Kiai, Santri, Dan Kesetiaan Ilmiah: Kritik Terhadap Labelisasi Feodalisme Di Dunia Pesantren - Mufaizin Mufaizin; Holil Baitaputra; Junaidi Junaidi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This paper is a scholarly reflection on the perspective of certain groups who perceive the leadership system and social relations within Islamic boarding schools (pesantren) as a form of feudalism. The author argues that such an accusation stems from a misunderstanding of the pesantren’s scholarly culture, which is grounded in the values of adab (etiquette), sanad (intellectual lineage), and moral authority in knowledge. Through historical, cultural, and conceptual approaches, this paper asserts that the relationship between kiai (religious teachers) and santri (students) is not a political power relation, but rather a transformative bond rooted in spirituality and scholarship. The pesantren thus serves as an emancipatory educational space that integrates respect with intellectual liberation.